2013
DOI: 10.1007/s13404-013-0130-9
|View full text |Cite
|
Sign up to set email alerts
|

Soldering of non-wettable Al electrode using Au-based solder

Abstract: In manufacturing three-dimensional SiC power modules, the Al electrode of SiC power devices should be soldered to the substrate. However, the Al electrode is difficult to be bonded by a solder due to the naturally formed aluminum oxide on it. In this paper, we describe an effective approach for soldering the non-wettable Al electrode by fabricating a Au-stud bump in the Al electrode together with a Au-20 wt% Sn or Au-12 wt% Ge solder. The soldering initiated at the Au bump and spreaded on the Al electrode. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…A variety of materials systems combined with Au-Ge have been evaluated in the pertinent literature, including Al, [34] Ti/Ti-W, [17] W, [20,32] and glass. [17] Lang et al showed that it was possible to bond to an Al metalization creating strong joints, > 50 MPa, and with stable electrical performance results.…”
Section: Other Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…A variety of materials systems combined with Au-Ge have been evaluated in the pertinent literature, including Al, [34] Ti/Ti-W, [17] W, [20,32] and glass. [17] Lang et al showed that it was possible to bond to an Al metalization creating strong joints, > 50 MPa, and with stable electrical performance results.…”
Section: Other Systemsmentioning
confidence: 99%
“…[17] Lang et al showed that it was possible to bond to an Al metalization creating strong joints, > 50 MPa, and with stable electrical performance results. [34] Long-term evaluation or other stress tests of that system was not 222 performed, and one might suspect that the Al-Au-Ge 223 system may form the well-known problematic Al-Au 224 IMCs such as Al 2 Au (purple plague) and Al 2 Au 5 (white 225 plague). [55] 226 IV.…”
Section: Other Systemsmentioning
confidence: 99%
See 3 more Smart Citations